Drag and lift contribution to the incipient motion of partly submerged flooded vehicles. (August 2015) - Arrighi, C.; Alcèrreca-Huerta, J.C.; Oumeraci, H.; Castelli, F.
Abstract: At present, the vehicles instability during an urban flood is recognized as being one of the most exacerbating factors for flood risk, particularly for people׳s safety. In this work, the incipient motion conditions of flooded vehicles are investigated and discussed. A mobility parameter θ V is here introduced as a function of the Froude number of the flow. A 3-dimensional numerical model describing the flow for different regimes past a specific vehicle geometry is presented to clarify the contribution of drag and lift forces to the incipient motion conditions. The results highlight the strong influence of the Froude number on the forces with a different dependence on it of drag and lift coefficients. The numerical results are compared with recent experimental data found in literature on partially submerged vehicles. The comparison confirms the crucial role of the friction coefficient and reveals the uncertainties introduced by the assumption of the car as a rigid body. The estimated force coefficients may provide a useful tool for flood risk assessment and management in urban areas.